A Challenging Case of Recurrent Nocturnal Tongue Biting in an Infant - Rodrigues, Jorge (2022)
Sleep disorders are common in children and adolescents, with a major impact on their quality of life. Although considered a likely sign of an underlying sleep or neurological disorder, nocturnal awakenings are usually of psychogenic or behavioral nature. Clinical history, physical examination, brain imaging, and polysomnographic studies can be necessary to establish an appropriate differential diagnosis, particularly in the presence of alarm signs. Tongue biting is considered to be highly suggestive of an epileptic seizure, justifying the exclusion of this diagnosis, although it may occur in psychogenic events and sleep-related movement disorders as well, such as geniospasm or facial myoclonus. This study presents a curious and challenging case of recurrent tongue biting during sleep of unknown etiology.